Strobe Glasses in Neuro-Optometric Rehabilitation of Homonymous Hemianopsia Following Severe Traumatic Brain Injury: A Case Report. - Friman, Ronit (Optometry & Visual Performance, 2026)
Background: Homonymous hemianopsia (HH) is a common visual consequence of traumatic brain injury (TBI), significantly affecting spatial awareness, visual scanning, and mobility. Neurovision rehabilitation (NVR) addresses visual efficiency and perceptual deficits; however, the integration of strobe glasses as an adjunctive modality in this population remains underexplored. Case Report: This case report describes a 22-yearold female patient with severe TBI and right HH who presented with impaired visual tracking, reduced scanning efficiency, and compromised mobility. Initial treatment included therapeutic anti-fatigue lenses (+0.85 D OU) with 3 base-up yoked prism, followed by 48 weekly in-office NVR sessions and home-based activities. NVR initially targeted core oculomotor, accommodative, binocular, and perceptual functions, later integrating strobe glasses to enhance scanning and engage residual vision near the scotoma. Strobe therapy began with full-lens strobe stimulation to support visual-motor coordination. Subsequently, a bi-left lens occlusion setting was applied, blocking the left half side of each lens, to promote further compensatory rightward scanning. The intervention aimed to improve perceptual awareness, reaction time, and adaptive spatial processing. While the visual field did not improve, the patient demonstrated functional gains, including enhanced scanning toward the blind field, improved navigation confidence, increased reading endurance, and better eye-hand coordination. Conclusion: Strobe glasses may be a valuable adjunct to conventional NVR for TBI patients with HH, supporting compensatory strategies and neuroplasticity. Further research is warranted to standardize protocols and investigate long-term outcomes across varied clinical populations.